Effects of material nonlinearity on the global analysis and stability of stainless steel frames. (January 2019) - Walport, F.; Gardner, L.; Real, E.; Arrayago, I.; Nethercot, D.A.
Abstract: In structural frames, second order effects refer to the internal forces and moments that arise as a result of deformations under load (i.e. geometrical nonlinearity). EN 1993-1-1 states that global second order effects may be neglected if the critical load factor of the frame αcr is greater than or equal to 10 for an elastic analysis, or greater than or equal to 15 when a plastic global analysis is used. No specific guidance is provided in EN 1993-1-4 for the design of stainless steel frames, for which the nonlinear stress-strain behaviour of the material will result in greater deformations as the material loses its stiffness. A study of the effects of material nonlinearity on the stability of stainless steel frames is presented herein. A series of different frame geometries and loading conditions are considered. Based on the findings, proposals for the treatment of the influence of material nonlinearity on the global analysis and design of stainless steel frames are presented. Highlights: Review of current design provisions for the global analysis of stainless steel structures presented; Benchmark results for frames generated using geometrically and materially nonlinear analyses with imperfections (GMNIA); Current design approaches for stainless steel frames assessed against benchmark GMNIA results; Proposals made for treatment of influence of material nonlinearity on global analysis and design of stainless steel frames.